2013
DOI: 10.1111/ter.12070
|View full text |Cite
|
Sign up to set email alerts
|

Indo‐Antarctic derived detritus on the northern margin of Gondwana: evidence for continental‐scale sediment transport

Abstract: Provenance studies from Cambro‐Ordovician sediments of the North Gondwana passive margin typically ascribe a North African source, a conclusion that cannot be reconciled with all observations. We present new U‐Pb ages from detrital rutile and zircon from Late Ordovician sediments from Saxo‐Thuringia, Germany. Detrital zircons yield age populations of 500–800 Ma, 900–1050 Ma and 1800–2600 Ma. The detrital rutile age spectra are unimodal with ages between 500 and 650 Ma and likely represent, together with the 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Ordovician orthogneisses are emplaced in Cambrian or older metamorphosed successions that might be regarded as sources of quartz-tectonite Black Flysch pebbles. The zircon provenance and signature of these rocks (Castiñeiras et al, 2008;Martínez et al, 2011) highlights a Gondwanan affinity and can be linked to North African cratons and orogenic belts through paleogeographic models of variable complexity (Avigad et al, 2012;Bea et al, 2010;Linnemann et al, 2011;Morag et al, 2011;Nance et al, 2008;Rösel et al, 2014;Shaw et al, 2014).…”
Section: The Pyrenees As Source Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Ordovician orthogneisses are emplaced in Cambrian or older metamorphosed successions that might be regarded as sources of quartz-tectonite Black Flysch pebbles. The zircon provenance and signature of these rocks (Castiñeiras et al, 2008;Martínez et al, 2011) highlights a Gondwanan affinity and can be linked to North African cratons and orogenic belts through paleogeographic models of variable complexity (Avigad et al, 2012;Bea et al, 2010;Linnemann et al, 2011;Morag et al, 2011;Nance et al, 2008;Rösel et al, 2014;Shaw et al, 2014).…”
Section: The Pyrenees As Source Areamentioning
confidence: 99%
“…Stenian-Tonian zircons are usually detrital grains supposed to have traveled from distant sources (Avigad et al, 2012;Kydonakis et al, 2014;Linnemann et al, 2011;Meinhold et al, 2011;Morag et al, 2011;Rösel et al, 2014), where zircons of similar ages are found in their original igneous host rocks. Notwithstanding, its finding has been pivotal to several paleogeographic and paleotectonic reconstructions (e.g.…”
Section: The Pyrenees As Source Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The products of the short-lived but intense Late Ordovician glacial event in Gondwana are best exposed in north-central Africa (Morocco [Destombes et al 1985;; Le Heron and Craig 2008], Algeria and Nigeria [Beuf et al 1971;Biju-Duval et al 1981;Linnemann et al 2011;, Libya [Massa 1988;Ghienne et al 2003;Le Heron and Craig 2008;Le Heron et al 2010], Niger [Denis et al 2006]), western Africa (Mauritania [Deynoux et al 1985;Willefert 1988; Ghienne and Deynoux 1998], Sierra Leone [Tucker and Reid 1973]), South Africa (Lesotho, Swaziland [Hiller 1992]), Arabia (Oman [Martin et al 2008], Jordan [Abed et al 1993;Turner et al 2005], Saudi Arabia [Vaslet 1990;McGillivray and Husseini 1992;Paris et al 2000;Clark-Lowes 2005], Iran [Ghavidel-syooki et al 2011]), South America (Brazil, Argentina [Caputo 1988;Martinez 1998;Astini 2003]), and Europe (Spain [Fortuin 1984;Gutiérrez-Marco et al 2010], Germany [Rösel et al 2014], France [Robardet and Dore 1988], Czech Republic [Śtorch 2006], Italy ], Turkey [Monod et al 2003;Ghienne et al 2010]; fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…U-Pb age dating of detrital rutile is a new approach in provenance studies and has, until now, only been applied in Phanerozoic sediments (e.g. Okay et al, 2011;Meinhold et al, 2011;Bracciali et al, 2013;Rösel et al, 2014). This contribution is the first to describe a U-Pb age study of detrital rutile in Palaeoproterozoic sediments and highlights its potential for other weakly metamorphosed Palaeoproterozoic sedimentary sequences.…”
Section: Introductionmentioning
confidence: 96%